1995
DOI: 10.1172/jci118150
|View full text |Cite
|
Sign up to set email alerts
|

The potent bone-resorbing mediator of Actinobacillus actinomycetemcomitans is homologous to the molecular chaperone GroEL.

Abstract: Actinobacillus actinomycetemcomitans is a Gram-negative bacterium implicated in the pathology of localized juvenile periodontitis, a condition involving rapid destruction of alveolar bone. We have established that gentle extraction of this bacterium in saline releases a proteinaceous fraction (which we have termed surface-associated material [SAM]) which has potent osteolytic activity in the murine calvarial bone resorption assay. Fractionation of the SAM has now revealed that activity is associated with a 62-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
112
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(115 citation statements)
references
References 31 publications
2
112
0
1
Order By: Relevance
“…The author's group have shown a relationship between circulating Hsp60 and cardiovascular disease, and this may relate to the influence of these proteins on macrophage function (Lewthwaite et al 2002b;Halcox et al 2005;Shamaei-Tousi et al 2007b) The in vivo breakdown of bone is driven by a specific monocyte population known as the osteoclast. Gramnegative bacterial Hsp60 proteins have been shown to stimulate both osteoclast formation and activation (Kirby et al 1995;Reddi et al 1998) as has human Hsp60 (Meghji et al 2003). However, it was found that the homologous proteins (Hsp60.2) from Mycobacterium tuberculosis and Mycobacterium leprae had no such activity (Kirby et al 1995).…”
Section: Hsp60mentioning
confidence: 99%
See 2 more Smart Citations
“…The author's group have shown a relationship between circulating Hsp60 and cardiovascular disease, and this may relate to the influence of these proteins on macrophage function (Lewthwaite et al 2002b;Halcox et al 2005;Shamaei-Tousi et al 2007b) The in vivo breakdown of bone is driven by a specific monocyte population known as the osteoclast. Gramnegative bacterial Hsp60 proteins have been shown to stimulate both osteoclast formation and activation (Kirby et al 1995;Reddi et al 1998) as has human Hsp60 (Meghji et al 2003). However, it was found that the homologous proteins (Hsp60.2) from Mycobacterium tuberculosis and Mycobacterium leprae had no such activity (Kirby et al 1995).…”
Section: Hsp60mentioning
confidence: 99%
“…Gramnegative bacterial Hsp60 proteins have been shown to stimulate both osteoclast formation and activation (Kirby et al 1995;Reddi et al 1998) as has human Hsp60 (Meghji et al 2003). However, it was found that the homologous proteins (Hsp60.2) from Mycobacterium tuberculosis and Mycobacterium leprae had no such activity (Kirby et al 1995).…”
Section: Hsp60mentioning
confidence: 99%
See 1 more Smart Citation
“…We then showed that the E. coli Cpn60 protein, GroEL, was a potent stimulator of bone resorption. However, neither the M. tuberculosis nor the M. leprae Cpn60.2 protein was able to induce bone resorption (22). Further investigation of the mycobacterial chaperonins revealed that neither of the two Cpn60 proteins produced by M. tuberculosis could stimulate bone resorption.…”
Section: Discussionmentioning
confidence: 94%
“…Bacterial infections cause conlmon bone diseases such as the periodontal diseases (with a prevalence of 10-150/0 worldwide), osteolnyelitis, bacterial arthritis and tuberculosis of bone. The first evidence that cpns could cause bone pathology was the finding that the cpn 60 of the oral pathogen, Act;lZobaciIIus actill011ryceten1C0l1zitails could cause bone resorption in vitro (Kirby et al, 1995). These studies found that groEL was a potent stimulator of bone resorption but that the cpn 60 molecules of Mycobacteritl1n spp.…”
Section: Bolle Diseasesmentioning
confidence: 99%